An Adapted Great Leaps Reading Intervention's Influence on Letter Sound Fluency and Oral Reading Fluency - Birkhofer, Jennifer A. (My University, 2014)
Early intervention for struggling readers is essential for developing fluency and more complex reading skills. One supplemental reading program that demonstrates research support is the Great Leaps Reading Program (Mercer & Campbell, 1998). The current study implemented an adaptation of the Great Leaps K-2 Reading Program to provide targeted interventions to four participants in an individual setting to determine whether training in pre-reading skills would result in improvement in letter sound fluency (LSF) and oral reading fluency (ORF). In addition, this study examined whether changing the Great Leaps activities to incorporate practice reading connected text would increase students' ORF. Results suggest that the students' LSF skills benefitted from this modified intervention. Not all of the students demonstrated gains in ORF. Limitations, implications for practice, and directions for future research are discussed.
Keywords: Great Leaps Reading Program; Oral reading--Psychological aspects; Reading, Psychology of; Response to intervention (Learning disabled children); Fluency (Language learning)